PREPARATION AND CHARACTERIZATION OF ACTIVATED CARBON FROM AFRICA STAR APPLE (Chrysophyllum albidum) SEED SHELL - Shuaib, Muhammad Mubarak; Musah, M.; Mathew, J. T. (FUDMA Journal of Sciences, 2024)
Activated carbon are carbonized materials with high surface area and porosity. This research explores the use of two stages: carbonization of the Africa star apple (C. albidum) seed shell followed by activation at 600 °C with sulphuric acid. The prepared activated carbon (AC) was characterized using scanning electron microscope and energy dispersive X-ray spectra (EDX), Fourier transform infrared, thermo-gravimetric analyzer, Brunauer-Emmett-Teller and X-ray diffraction (XRD) for its surface morphology with its elemental composition, functional groups, thermal stability, specific surface area and porosity and its crystalline structure respectively. Based on the analysis, the activated carbon contains highly irregular and jagged surface, characteristic of activated carbon material with active surface properties due to the functional groups. The EDX spectrum and elemental report of the activated carbon indicates a significant concentration of carbon atoms within the activated carbon sample. XRD pattern of activated carbon presents the existence of a specific crystallographic plane which implies the presence of well-organized layers of carbon atoms in the AC structure. The surface area of the activated carbon is determined to be 47.129 m²/g with pore volume of 0.08712 cc/g. A high surface area is indicative of a large number of available adsorption sites, which is advantageous for adsorption processes. Therefore, Chrysophyllum albidum is an apt agricultural by product for the preparation of high-quality activation carbon.